Functional heartburn: problems of diagnosis and treatment - Vadim A. Akhmedov; Galiya R. Bikbavova; Maria S. Tsibulkina (Лечащий Врач, 2024)
Background. Functional heartburn is one of the disorders of the gastrointestinal tract that is widespread in modern society. The disease is characterized by refractory symptoms of heartburn, lack of relief of symptoms with optimal use of proton pump inhibitors, which requires differential diagnosis with a number of diseases of the esophagus. Functional heartburn is associated with frequent medical treatment, repeated examinations, and increased insurance costs. At the same time, there is a problem of insufficient awareness of doctors about this disease, the lack of a widely available diagnostic method, which leads to a failure to receive effective treatment and a decrease in the quality of life of patients. The disease is often associated with anxiety and depressive disorders, the growth of which has been noted recently, which requires timely diagnosis and correction of these conditions. Visceral hypersensitivity is a key part of the pathophysiology of functional heartburn, and psychosocial factors influence interactions between the gastrointestinal nervous system and the brain, which determines the severity of symptoms in patients. Doctors are recommended to tell patients in detail about the essence of the diagnosis, directions in possible effective treatment, for better adherence to therapy, the use of antidepressants, cognitive behavioral therapy, hypnotherapy and relaxation methods is recommended. At the moment, the standard for the diagnosis of functional heartburn is pH-impedance measurement, with the primary exception of organic pathology during endoscopic examination of the esophagus with biopsy and histological examination, and the exclusion of esophageal motility disorders during manometry. Non-invasive, affordable and cost-effective diagnostic tools are needed to avoid overdiagnosis of gastroesophageal reflux disease and improper use of proton pump inhibitors, saliva pepsin examination and dental examination are promising.Objective. The purpose of the review is to summarize the existing research data on the prevalence of functional heartburn, the influence of psychological factors on its course, and current methods of diagnosis and treatment of this pathology. In order to identify studies on the problems of diagnosis and treatment of functional heartburn, a literature search was conducted in the PubMed and eLibrary databases until November 2023, original articles, meta-analyses and relevant reviews were reviewed.